2015
DOI: 10.1007/s00382-015-2758-z
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between tropospheric temperature and Indian summer monsoon rainfall as simulated by RegCM3

Abstract: during the contrasting monsoon years are also close to their respective observed values. Temporal CCs between the TT over Tibet, Pakistan and Central India during the summer monsoon season and gridded ISMR values reveals that the TT over Pakistan has been better correlated with the ISMR than those over Tibet and Central India. This relationship has been well supported by the model simulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…IMD data are also validated against another observational data set namely APHRODITE (Yatagai et al ., ) and are found to be nearly identical (Rajeevan and Bhate, ). The IMD data set is used in numerous works to study various observed dynamical aspects of ISM precipitation (Roja Raman et al ., ; Panda et al ., ; Panda and Kumar, ; Prakash et al ., ; Rai et al ., ) as well as a reference in evaluation of climate models (Das et al ., ; Kumar et al ., ; Pattnayak et al ., ; ; Das et al ., ; Maharana and Dimri, ; ; Dash et al ., ). Furthermore, it is available at a resolution of 0.5° which matches with that of CORDEX‐SA RCMs that are considered for bias correction here.…”
Section: Methodsmentioning
confidence: 99%
“…IMD data are also validated against another observational data set namely APHRODITE (Yatagai et al ., ) and are found to be nearly identical (Rajeevan and Bhate, ). The IMD data set is used in numerous works to study various observed dynamical aspects of ISM precipitation (Roja Raman et al ., ; Panda et al ., ; Panda and Kumar, ; Prakash et al ., ; Rai et al ., ) as well as a reference in evaluation of climate models (Das et al ., ; Kumar et al ., ; Pattnayak et al ., ; ; Das et al ., ; Maharana and Dimri, ; ; Dash et al ., ). Furthermore, it is available at a resolution of 0.5° which matches with that of CORDEX‐SA RCMs that are considered for bias correction here.…”
Section: Methodsmentioning
confidence: 99%
“…The experiments conducted by Giorgi and Marinucci (1996) with different topography indicated that resolution has a greater impact on the simulation through the model physics and dynamics rather than through the topography itself, especially for summer convection. The RegCM version 3 (RegCM3) has also been successfully integrated to simulate the salient features of Indian summer monsoon circulation and rainfall (Dash et al 2013;Pattnayak et al 2013aPattnayak et al , 2016b. Dash et al (2006) has shown that the RegCM3 simulates intraseasonal variability of Indian summer monsoon rainfall over India reasonably well during the period 1993-1996.…”
Section: Introductionmentioning
confidence: 99%
“…ISMR exhibits significant temporal and spatial variability (Mooley and Parthasarathy 1984;Thapliyal and Kulshrestha 1991;Kripalani and Kulkarni 2001;Sahai et al 2003;Naidu et al 2015). Several scientists have investigated the inter-annual and intra-seasonal variations of monsoon rainfall and the associated phenomena over the last several years using observed data (Webster et al 1998;Gadgil et al 2003) and conducting modeling studies (Ratna et al 2011;Satyanarayana and Kar 2016;Pattnayak et al 2016a). The key features of Indian summer monsoon include the sudden onset and gradual withdrawal, which signify the beginning and end of the rainy season respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In 24 years out of the 30 years, the bias is less than 2 days. In the summer monsoon rainfall contrasting years such as 1982 and 1983, 1987 and 1988, 2002 and 2003 (Pattnayak et al, ; Pattnayak et al, ), the onset dates simulated by RegCM4 are close to observed onset dates. The aim of presenting the MOK and all India summer monsoon rainfall on the same plot (Figure a) is to show the relation between these two.…”
Section: Resultsmentioning
confidence: 63%